The Role Of Legal Sociology In Implementing PPP (Public-Private Partnership) (Lhok Guci PPP Case Study) - Kurdi Kurdi (Fakultas Hukum Dehasen, 2024)
Legal products can be used as a means of improving infrastructure development in Indonesia. The preparation of legal products must be in accordance with the conditions and desires of society and in connection with this, the branch of science that can be used is called legal sociology. The implementation of the PPP (Public-Private Partnership) scheme in Indonesia has shown a significant impact in providing infrastructure. Starting from the need for a legal sociological view of the implementation of infrastructure development with a PPP financing scheme, the author wants to study it further. This research aims to determine the role of legal sociology in implementing PPP (Public-Private Partnership). This research is included in the type of normative research with a statute approach and conceptual approach. The results of the research show that the application of legal sociology in the implementation of PPP, especially the Lhok Guci PPP, can be used as a means of assessing legal effectiveness, revealing ideology and interests and also legal sociology can be used to assess the identification of cultural and religious influences in the implementation of infrastructure development carried out using PPP financing schemes.